Methicillin resistant Staphylococcus aureus - an overview - Haque, N; Bari, MS; Bilkis, L; Haque, N; Haque, S; Sultana, S (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Jan;20(1):159-164 The abstract of this article is available on the PubMed website